Application Study on Fiber Optic Monitoring and Identification of CRTS-II-Slab Ballastless Track Debonding on Viaduct - Gaoran Guo (Applied Sciences, 2021)
China Railway Track System (CRTS)-II-slab ballastless track is a new type of track structure, and its interlayer connection state is considerably important for the operation safety and ride comfort of high-speed trains. However, the location and multiple influencing factors of interlayer debonding lead to difficulties in monitoring and identification. Here, the research on the design and application of a monitoring scheme that facilitates interlayer debonding detection of ballastless track and an effective indicator for debonding identification and assessment is proposed. The results show that on-site monitoring can effectively capture the vibration signals caused by train vibration and interlayer debonding. The features of the data acquired in the situations with and without interlayer debonding are compared after instantaneous baseline validation. Some significant features capable of obviously differentiating a debonding state from the normal state are identified. Furthermore, a new indicator, combining multiple debonding-sensitive features by similarity-based weights normalizing the initial difference between mutual instantaneous baselines, is developed to support rational and comprehensive assessment quantitatively. The contribution of this study includes the development and application of an interlay-debonding monitoring scheme, the establishment of an effective-feature pool, and the proposal of the similarity-based indicator, thereby laying a good foundation for debonding identification of ballastless track.